Esterification Of Octanoic Acid And Ethanol Using Sulfated Zirconia In The Presence Of Triglycerides: Kinetic And Modelling Study - Bryan Lester, Binar (2009)
The esterification of octanoic acid and ethanol using sulfated zirconia in the presence of triglycerides is one of the methods to produce biodiesel. As the fuel used today, petroleum is estimated depleted around 30-45 years in the future, Biodiesel is an alternative biofuel that can be produced using esterification method. The esterification of octanoic acid is done to determine the best operation condition to yield better conversion of octanoic acid. The operation conditions for the esterification of octanoic acid are temperature of reaction, amount of sulfated zirconia used, amount of triglycerides presence and molar ratio of octanoic acid to ethanol. The temperature of reaction ranged from 30ºC to 50ºC. The amount of sulfated zirconia used ranged from 0.5g to 1.5g. The amount of triglycerides presence ranged from 30ml to 70ml. The molar ratio of octanoic acid to ethanol ranged to 1:1 to 1:5. The best operating condition achieved for the esterification of octanoic acid and ethanol were 30ºC reaction temperature, 1.5g sulfated zirconia used, 1:1 molar ratio of octanoic acid to ethanol and 50ml of triglycerides presence in the esterification. The kinetic model been used is pseudo-homogeneous kinectic model based on the experimental data gained. The pseudo-homogeneous kinetic model gives a good agreement between the experimental data and the model used.